Release of potassium in association with structural evolution during biomass combustion. (1st March 2021) - Cao, Wenhan; Li, Jun; Lin, Leteng; Zhang, Xiaolei
Highlights: Increasing the heating rate of biomass can promote potassium release. A three-stage potassium release mechanism is defined as a function of temperature. Potassium compounds exist inside biomass structure are mostly inorganic salts. SEM-EDX mapped up potassium transition with the structural evolution of biomass. Abstract: A mechanistic understanding of potassium release is essential to mitigate the potassium-induced ash problems during biomass combustion. This work studies the effects of operational condition on the potassium release and transition during the combustion of wheat straw, and elucidate the release potential of potassium associated with the structural change of biomass particles. The combustion tests were carried out in a laboratory-scale reactor, working in a wide range of temperatures and heating rates. It was found that the combustion of biomass sample at a temperature up to 1000 °C results in a release of over 60% of its initial potassium content. Raising the heating rate from 8 °C/min to 25 °C/min could lead to an additional release of up to 20% of the initial amount of potassium. A three-stage potassium release mechanism has been concluded from this work: the initial-step release stage (below 400 °C), the holding stage (400–700 °C) and the second-step release stage (above 700 °C). Comprehensive morphology analysis with elemental (i.e. K, S, O, Si) distribution was carried out; the results further confirmed that potassium is likely to exist inside the stem-like tunnel of biomass particles, mainly in forms of inorganic salts. During the heating-up process, the breakdown and collapse of biomass particle structure could expose the internally located potassium and thus accelerate the release of potassium and the transform of its existing forms. Lastly, a detailed temperature-dependent release mechanism of potassium was proposed, which could be used as the guidance to mitigate the release of detrimental potassium compounds by optimising the combustion process.